Peran NGO dalam Dinamika Isu Perubahan Iklim di Afrika - Harison, Stevie Leonard (Global: Jurnal Politik Internasional, 2010)
Climate change has become one of the most challenging issues for the international system in this 21st century because its negative impact has been founded in every regions in the world. One of those is Africa with its far-lagged begind and poorer performance in political, economic, and social sectors than any other parts of the world. This article tries to analyze the ongoing process of the creation of good governance in Africa's climate change dynamics. In Africa, the progress of civil society activism is predicted to be the more important factor than the policy outcome from its government in making good governance. In this context, the rise of civil society should be better understood as being an equal partner than a competitor to the policy-makers to have more intensive cooperation and collaboration to solve the urgent climate problems in Africa at present.